Biodegradable Levan/Chitosan Composite Films: Development and Application in Beef Filet Packaging - Anissa Haddar; Emna Sellami; Oumayma Bouazizi; Assaad Sila; Ali Bougatef (Foods)
This study developed biodegradable levan–chitosan composite films for beef filet packaging, optimizing their functional properties and assessing their efficacy in food preservation. Films were prepared via solution casting using varying levan–chitosan ratios (100:0, 75:25, 50:50, 25:75, 0:100) with glycerol (30%) as a plasticizer. The L25:C75 formulation exhibited superior mechanical properties (tensile strength: 15.43 ± 0.04 MPa; elongation at break: 35.37 ± 1.12%) and high-water solubility (46.64 ± 0.37%). FTIR analysis confirmed intermolecular interactions between levan and chitosan. The films demonstrated strong antioxidant activity (91% ABTS•+ inhibition) and broad-spectrum antibacterial effects, with inhibition zones of 18 ± 0.30 mm against E. coli and 16 ± 0.20 mm against S. aureus. When applied to beef filets stored at 4 °C for 7 days, the L25:C75 films reduced total viable bacterial counts by 1.8 log CFU/g compared to LDPE packaging. Biodegradability tests revealed a 68% degradation rate for high-levan films (L75:C25) after 14 days in soil. These results highlight the potential of levan–chitosan films as sustainable, active packaging materials to extend food shelf life while addressing environmental concerns.